Evaluasi Proses Bisnis Administrasi Akademik pada Institusi ABC dengan menggunakan Quality Evaluation Framework (QEF) - Troy Kornelius Daniel; Andi Reza Perdanakusuma; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
ABC Higher Education Institute is an Educational institution located in Pare, Kediri, East Java. ABC Institute of Higher Education has a process or flow in mail management for student needs. During the Covid-19 pandemic in 2020, ABC Higher Education began implementing an online mailing system, but it did not yet have a clear process flow. Based on these problems, the author raises the topic of business processes in the administrative department and focuses on the management of Research Licenses, street vendors, and Student Activity Signs. The Quality Evaluation Framework (QEF) method is used by authors to conduct research on the quality level of mail management business processes for student needs. Based on the results of research on the online student letter management process, it was found that there are parameters that do not run according to the target, namely timeliness. From the results of the evaluation, a problem-root analysis was then carried out. In this study, analyze the root cause using the 5 Whys method. The use of the 5 Whys method is to give a series of